2022
DOI: 10.1111/mcn.13362
|View full text |Cite
|
Sign up to set email alerts
|

The impact of a package of behaviour change interventions on breastfeeding practices in East Java Province, Indonesia

Abstract: Suboptimal infant young child feeding practices are frequently reported globally, including in Indonesia. This analysis examined the impact of a package of behaviour change interventions on breastfeeding practices in Malang and Sidoarjo Districts, East Java Province, Indonesia. The BADUTA study (which in the Indonesian Language is an acronym for BAwah DUa TAhun, or children aged less than 2 years) was an impact evaluation using a cluster-randomized controlled trial with two parallel treatment arms. We conducte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 30 publications
1
6
0
1
Order By: Relevance
“…The cadres state that home visits are an effective intervention to overcome stunting children based on individual problems. This is also supported by previous studies aimed at solving the problem of the COVID-19 severity [38], [39], obesity, and DM during the pandemic [40], increasing the promotion of breastfeeding, IYCF, and growth children [14].…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…The cadres state that home visits are an effective intervention to overcome stunting children based on individual problems. This is also supported by previous studies aimed at solving the problem of the COVID-19 severity [38], [39], obesity, and DM during the pandemic [40], increasing the promotion of breastfeeding, IYCF, and growth children [14].…”
Section: Discussionsupporting
confidence: 81%
“…In terms of coherence, short course interventions and home visit assistance for stunting children are closely related to the ongoing program. To increase mothers' knowledge and skills, they should be aware and empowered on means of caring for their children [14]. This research location is the epicenter of stunting, therefore, when the intervention ends, the local government can implement this program as a long-term home visit until there are no more cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The assistance rendered to families with children at risk of stunted growth is comprehensive, and comprises detailed measures aiming to overcome malnutrition and other health problems. Furthermore, several studies have shown that assistance is effective in increasing dietary diversity scores and identifying malnutrition [ 12 ], improving healthcare access [ 13 ], increasing breastfeeding success [ 14 ], reducing early complementary feeding for children [ 14 ], promoting healthy practices [ 15 ], increasing body weight, and improving children development [ 16 ]. The Indonesian Presidential Regulation Number 72 of 2021 addresses the subject of aiding families at risk of stunting with the aim of improving access to information and services through counseling, referral services facilitation, and social assistance programs [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Breastfeeding is recognized globally as an essential component of infant and young child feeding (IYCF) practices (Dorri et al, 2022;Titaley et al, 2022). The World Health Organization (WHO) and the United Nations International Children Fund (UNICEF), having recognized the sundry benefits of breastfeeding, developed the Global Strategy for IYCF, which aims to promote safe and appropriate IYCF practices (WHO, 2021).…”
Section: Introductionmentioning
confidence: 99%